2017
DOI: 10.3390/ijms18030680
|View full text |Cite
|
Sign up to set email alerts
|

Survivin and NAIP in Human Benign Prostatic Hyperplasia: Protective Role of the Association of Serenoa repens, Lycopene and Selenium from the Randomized Clinical Study

Abstract: Benign prostatic hyperplasia (BPH) treatment includes the apoptosis machinery modulation through the direct inhibition of caspase cascade. We previously demonstrated that Serenoa repens (Ser) with lycopene (Ly) and selenium (Se) reawakened apoptosis by reducing survivin and neuronal apoptosis inhibitory protein (NAIP) levels in rats. The aim of this study was to evaluate the effectiveness of Ser-Se-Ly association on survivin and NAIP expression in BPH patients. Ninety patients with lower urinary tract symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
(46 reference statements)
2
6
0
2
Order By: Relevance
“…The development of BPH is closely associated with dysregulation of androgens, increased proliferation and decreased apoptosis of cells in the prostate. This is approved in our study that showed significant decrease of apoptotic marker (caspase3) in group III and this finding is supported by previous studies . Group IV showed highly over expressed caspase3 explaining marked apoptotic features, damage and death of prostatic tissue.…”
Section: Discussionsupporting
confidence: 92%
“…The development of BPH is closely associated with dysregulation of androgens, increased proliferation and decreased apoptosis of cells in the prostate. This is approved in our study that showed significant decrease of apoptotic marker (caspase3) in group III and this finding is supported by previous studies . Group IV showed highly over expressed caspase3 explaining marked apoptotic features, damage and death of prostatic tissue.…”
Section: Discussionsupporting
confidence: 92%
“…After three months, there was a decrease in survivin and NAIP, while caspase-3 was significantly increased in BPH patients treated with SeR-Se-LYC, in comparison with the placebo group. This combination of compounds also reduced PSA and prostate-specific membrane antigen (PSMA) expression [ 75 ]. It has been hypothesized that SeR, LYC, and Se, administered together, can amplify their therapeutic efficacy also in terms of counteracting the inflammatory component of BPH.…”
Section: Carotenoids and Prostatic Physiology And Pathology (Othermentioning
confidence: 99%
“…Besides, the reason why varicocele impacted the function of testis and epididymis was still indefinite. Lycopene was reported as a safe nontoxic natural extract with antioxidative and anti-inflammatory effects [6], which was used to treat the chronic prostatitis and/or chronic pelvic pain syndrome (CP/CPPS), benign prostatic hyperplasia (BPH), and prostate cancer as a supplementary treatment [7][8][9]. In earlier studies, researchers found that oxidative stress [2] and hypoxia [10] due to varicocele were considered to contribute to the hypoxia-induced testicular injury.…”
Section: Introductionmentioning
confidence: 99%